2019 Joint Conference of the IEEE International Frequency Control Symposium and European Frequency and Time Forum (EFTF/IFC) 2019
DOI: 10.1109/fcs.2019.8856061
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability Analysis Towards < 10-14 Level for a Highly Compact POP Rb Cell Atomic Clock

Abstract: Long-term frequency instabilities in vapor-cell clocks mainly arise from fluctuations of the experimental and environmental parameters that are converted to clock frequency fluctuations via various physical processes. Here, we discuss the frequency sensitivities and the resulting stability limitations at one-day timescale for a rubidium vapor-cell clock based on a compact magnetron-type cavity operated in air (no vacuum environment). Under ambient laboratory conditions, the external atmospheric pressure fluctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We have also shown that in ambient laboratory conditions, the dominant contribution to clock instability may arise from ambient pressure fluctuations via the barometric effect [23]. A preliminary analysis of instability sources toward a complete long-term budget was presented in [19]. Here, we evaluate in detail the clock sensitivities to experimental and environmental parameter fluctuations and quantify the resulting clock stability limits on long-term timescales up to one day.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We have also shown that in ambient laboratory conditions, the dominant contribution to clock instability may arise from ambient pressure fluctuations via the barometric effect [23]. A preliminary analysis of instability sources toward a complete long-term budget was presented in [19]. Here, we evaluate in detail the clock sensitivities to experimental and environmental parameter fluctuations and quantify the resulting clock stability limits on long-term timescales up to one day.…”
mentioning
confidence: 97%
“…In the following, we present a detailed analysis and budget of the long-term instability for a highly compact rubidium vapor-cell clock, based on our preliminary analysis reported in [19]. The clock employs a time-domain Ramsey interrogation with laser optical detection.…”
mentioning
confidence: 99%